2013
DOI: 10.1002/brb3.184
|View full text |Cite
|
Sign up to set email alerts
|

Infants' object location and identity processing in spatial scenes: an ERP study

Abstract: BackgroundFast detection and identification of objects in an environment is important for using objects as landmarks during navigation. While adults rapidly process objects within an environment and use landmarks during navigation, infants do not routinely use distal landmarks below the age of 18 months. In the current event-related potential (ERP) study we adopted an oddball paradigm to examine whether infants are capable of processing objects in environments, which is a prerequisite for using objects as land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…van Hoogmoed et al. () used an ERP oddball task and found that 12‐month‐old infants' ability to detect changes in object‐identity bindings in visual scenes was not fully developed. Importantly, in these previous studies, infants were given the opportunity to learn the location–identity relation over multiple trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…van Hoogmoed et al. () used an ERP oddball task and found that 12‐month‐old infants' ability to detect changes in object‐identity bindings in visual scenes was not fully developed. Importantly, in these previous studies, infants were given the opportunity to learn the location–identity relation over multiple trials.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that infants bind information in memory representations. In studies in which bindings were learned over successive trials (therefore tapping longer‐term memory systems), infants between 4 and 12 months of age show evidence of learning bindings—and responding to a violation in binding—although the evidence varies in terms of the kinds of features and the task (Mareschal & Johnson, ; Newcombe, Huttenlocher, & Learmonth, ; van Hoogmoed, van den Brink, & Janzen, ). Indeed, developmental changes in the ability to bind features to objects stored in memory has been suggested as one possible mechanism underlying age‐related changes in infants' performance on tasks that require them to remember information about hidden objects (e.g., Wang & Baillargeon, ; Wilcox & Schweinle, ).…”
mentioning
confidence: 99%